2008
DOI: 10.1631/jzus.b071464
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an SMS text messaging and phone reminder to improve attendance at a health promotion center: A randomized controlled trial

Abstract: SMS and telephone are effective reminders for improving attendance rate at a health promotion center. SMS reminder may be more cost-effective compared with the telephone reminder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
181
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(194 citation statements)
references
References 22 publications
6
181
1
6
Order By: Relevance
“…Three studies demonstrated improvements in clinic attendance with text messaging reminders versus no reminder. In three studies, [38][39][40] studied the effectiveness of an Internet-based diabetes education program with SMS and e-mail reminders and found that only 77 (39%) of the treatment arm logged-on to the online education program, and of these subjects, 34 (44%) logged-on once, 12 (16%) logged-on twice, and 31 (40%) logged-on more than three times. When subjects were asked about the number of times they logged-on, 22 (14%) stated that they had used the Web site when in fact a log-in was not recorded.…”
Section: Process Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…Three studies demonstrated improvements in clinic attendance with text messaging reminders versus no reminder. In three studies, [38][39][40] studied the effectiveness of an Internet-based diabetes education program with SMS and e-mail reminders and found that only 77 (39%) of the treatment arm logged-on to the online education program, and of these subjects, 34 (44%) logged-on once, 12 (16%) logged-on twice, and 31 (40%) logged-on more than three times. When subjects were asked about the number of times they logged-on, 22 (14%) stated that they had used the Web site when in fact a log-in was not recorded.…”
Section: Process Of Carementioning
confidence: 99%
“…Chen et al 38 and Leong et al, 39 whose studies showed that SMS and telephone reminders improve appointment attendance rates, evaluated cost-effectiveness as a secondary outcome. SMS was found to be 35% and 45% less expensive, respectively, per attendance than telephone reminders.…”
Section: Costsmentioning
confidence: 99%
“…79,84 Successful contact is assumed when the mobile phone indicates "message sent" being received by the sender. 44,59,66 However, many patients may either not receive their SMS reminder or may receive and ignore a reminder that was not intended for them due to incorrect data entry on hospital systems. 77,79 Some clients may not receive their text message until after their scheduled appointment because of delays in delivery of the text or because their phones were switched off, out of battery or out of credit.…”
Section: Accuracy Of Patient Recordsmentioning
confidence: 99%
“…Moreover, while this intervention is thought to be cost effective in clinics with high baseline noshow rates, the efficacy is less clear when baseline no-show rates are low. 18,19,30,31 Nevertheless, even in practices with low baseline no-show rates, the risk of no-show is heterogeneous-that is, some patients are more likely of noshows than others. 9,10,28,29,[32][33][34] Prior work has effectively demonstrated that no-shows are predictable; validated models can accurately predict the likelihood that a patient will fail to keep a scheduled appointment.…”
Section: Introductionmentioning
confidence: 99%